Isolation And Characterization Of Genes Expressed In Early Flowering Tissues Of Teak (Tectona Grandis Linn. F) - Basherudin, Norlia (2007)
Teak is a highly sought-after timber species in the world, and therefore has been selected as one of the timber species for forest plantation in Malaysia. However, in Malaysia teak has been observed to flower as early as three years after planting. The early flowering leads to the forking phenomenon, which lowers the quality of the timber produced. This study was initiated in order to understand the genetic control of flower development in teak with the ultimate aim of being able to manipulate this process for improvement of the species. In the observations of flower development in teak two different types of shoots were identified, flowering and vegetative shoots. The difference gave an opportunity to isolate the genes expressed in flowering shoots using the PCR-subtractive hybridization method. Based on 130 clones isolated, 22% were functionally unknown and 13% to 15% each were involved in cell structure, signal transduction and transcription. The other clones, 1% to 10% each, were involved in energy, protein synthesis, protein digestion and storage, disease and defense, intracellular traffic and metabolism.Out of the 130 clones analyzed, two were chosen for further analysis. The clones were TFS3-B7, which is similar to Late Elongated Hypocotyls (LHY) gene and TFS3-B17, which is similar to Arabidopsis Shaggy kinase-11 (AtSK-11) gene. The full-length cDNA of TFS3-B7 was 2948 base pair (bp) and potentially encoded for 768 amino acids. It was named Tectona grandis LHY (Tg-LHY), as the gene was similar to the LHY gene of some species. The level of gene expression was found to be high four hours after dawn in flowering shoots and flower, which might indicate involvement of the circadian clock system in teak flower development. Temperature might be a potential environmental cue detected by the teak circadian clock system, as the temperature was found higher within three months before the flowering season occurred. The cDNA of Tg-LHY translated into a protein of about 110 kD in a prokaryotic expression system. The gene construct of Tg-LHY in GATEWAY expression vector was also transformed into Arabidopsis. GUS assay analysis indicated successful integration of reporter gene into the Arabidopsis genome. Arabidopsis transformation will be further investigated in the future. The second clone, TFS3-B17, with its cDNA of 1705 bp in length, was potentially encoded for 410 amino acids. The gene was named Tectona grandis Shaggy kinase (Tg-SK), as it was similar to Arabidopsis Shaggy kinase-11 (AtSK-11). Analysis of the gene structure showed that it had 11 introns, similar to the number of introns found in AtSK-11. The high similarity between Tg-SK and AtSK-11 within their kinase region and structure might indicate their similar function. In Arabidopsis, AtSK-11 gene has been suggested to play a role in meristem identity fate. Higher transcription level of this gene was detected in early and later stage of flower development, which was similar with what has been reported in Arabidopsis. Gene expression analysis in a prokaryotic system showed that Tg-SK cDNA translated into a protein of about 40 kD.